Aspek Kriminologi Dan Proses Mental Dalam Ruang Lingkup Psikologi Kepolisian - Suci Hidayah; Adelia Khoirunnisa Andari; Haniffah Maharani Azahra; Muhammad Rizki; Tugimin Supriyadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Criminology studies can be grouped into four aspects of discussion including crime, crime perpetrators, crime victims, and society's reactions to crime. The term criminology is taken from English, namely Criminology. Criminology itself comes from Latin which consists of two words, namely crimen which means criminal and logos which means knowledge. Thus criminology can be interpreted as the science of crime or criminals. The development of science has made a major contribution to the birth of Criminology, as a systematic collection of knowledge from various fields of study about crime and criminals.